Coloured and the stoppage of a racial mediation in South Africa - Ribeiro, Fernando Rosa (Revista de Antropologia, 1995)
Coloured as a racial calegory in Soulh Africa stands for a residual element that subverts and potentially threatens the essentialist system of race classification. Differently to Brazil, where mestiço was conceived as the point at which the racial system would be transcended through the ideology of "whitening", coloured (mestiços counterpart in South Africa) was everything the essentialist system could not classify. Instead of being the foundation of nationality as mestiço in Brazil , in South Africa coloured became a compartmentalized category justas "white" and "black". However, essentialist classification cannot deal satisfactorily with that category, for coloured can potentially subvert the whole system of classification. This article attempts to show the meaning of the category in present times as well as its origin in the colonial period.